(untitled) (European Journal of Formal Sciences and Engineering, 2022)
The paper is focused on the practical knowledge transfer problems in higher education engineering. The objective is to improve the knowledge transfer in order to facilitate rapid workplace integration. The curriculum and the practical training of students at University Politehnica Timisoara, Department of Automation and Applied Informatics are presented and discussed. The implication of companies in the students’ practical training is highlighted. A practical knowledge transfer system is proposed, based on logical distribution of the requirements for a single practical application, transversally, to the curriculum courses. The initial changes in the curriculum, introduced after the Bologna Declaration, are presented for the previously mentioned department. Ideas and questions were released which can be clarified, interpreted and criticized, providing a discussion base that can be benefic to the academic and industrial community. The presented changes were discussed with the economical zonal partners (companies: Continental Automotive, Hella, Nokia, Yazaki, Huf, Flextronics, etc.), being appreciated and sustained by the companies.